PATHOMORPHOLOGICAL CHANGES IN THE THYROID GLAND IN TOXIC DIFFUSE GOITER - S. KURBONOV; M.K. GULOV; I.A. DAVLATOV; E.H. TAGAYKULOV (Avicenna Tajik State Medical University, 2017)
Objective: To study the main pathomorphological and morphometric structural rearrangements of thyroid tissue (TT) formations in toxic diffuse goiter (TDG). Methods: By the methods of anatomical preparation and histological sections, macro and microscopic structural features of the thyroid gland were studied in 22 patients with TDG; both sexes aged 36 to 60 years, operated in the Department of General Surgery, State Clinical Hospital № 5, named by Academician K.T. Tadjiev Results: An analysis of the degree of progression of pathomorphological changes in the tissue and the follicular structure of the thyroid gland revealed a dependence on the duration and severity of the disease. The results of a quantitative study showed that the average diameter of the follicles, as compared with the norm (70.8±1.19 μm), became larger (80.8±1.26 μm). The height of the follicular epithelium for this pathology was 15.16±0.22 μm, with a norm of 10.06±0.09 μm (p<0.01). This led to a change in the Brown index, i.e. the more this index was, the lower the functional activity of the organ. Conclusion: The characteristic morphological signs of thyroid disease in TDG are lymphoplasmacytic infiltration of the stroma of the gland, activation of folliculogenesis and hyperplasia of the thyroid epithelium, which can lead to the development of functional thyroid disorders.